2016
DOI: 10.1021/acs.langmuir.6b01191
|View full text |Cite
|
Sign up to set email alerts
|

High Resistivity Lipid Bilayers Assembled on Polyelectrolyte Multilayer Cushions: An Impedance Study

Abstract: Supported membranes on top of polymer cushions are interesting models of biomembranes as cell membranes are supported on a polymer network of proteins and sugars. In this work lipid vesicles formed by a mixture of 30% 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) and 70% 1,2-dioleoyl-sn-glycero-3-phospho-l-serine (DOPS) are assembled on top of a polyelectrolyte multilayer (PEM) cushion of poly(allylamine hydrochloride) (PAH) and poly(styrene sodium sulfonate) (PSS). The assembly results in the formation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…[5] In particular, fused deposition modeling (FDM) allows the manufacturing of objects by the to minimize the amount of material used. [22,23] LbL has been widely used in the biomedical sector, including substrates with tunable properties for theranostics [24] or the design of micropatterned protein arrays. [25] LbL has exploited the use of polysaccharides to produce biodegradable LbL build-ups from bio-based materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] In particular, fused deposition modeling (FDM) allows the manufacturing of objects by the to minimize the amount of material used. [22,23] LbL has been widely used in the biomedical sector, including substrates with tunable properties for theranostics [24] or the design of micropatterned protein arrays. [25] LbL has exploited the use of polysaccharides to produce biodegradable LbL build-ups from bio-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18–20 ] This technology is known since 1997 [ 21 ] and consists in the fabrication of thin films via electrostatic or supramolecular interactions of different polymers, which allows to minimize the amount of material used. [ 22,23 ] LbL has been widely used in the biomedical sector, including substrates with tunable properties for theranostics [ 24 ] or the design of micropatterned protein arrays. [ 25 ]…”
Section: Introductionmentioning
confidence: 99%
“…26,36 Electrochemical impedance spectroscopy (EIS) is used to measure the complex impedance properties of a material and has been widely used to study interfacial interactions, such as antigen-antibody interaction, and cancer cell capture as well as for evaluation of biomembranes. 27,[37][38][39] EIS was implemented here at gold microcavity array substrates analogous in structure to the optically transparent PDMS arrays used for FCS. The combination of FLCS and EIS provides new insights into the dynamics of the membrane and impact of PP50 polymer on lipid membrane lateral packing and integrity in real time.…”
Section: Introductionmentioning
confidence: 99%
“…Bilayer formation takes place if the molar percentage of DOPS lies between 50 and 70%. Electrochemical impedance spectroscopy (EIS) studies performed by Diamanti et al 24 showed that the lipid bilayer assembled on PAH/PSS displayed high resistance values: 1.89 Â 10 7 O cm 2 . This resistance is comparable with the resistance of a black lipid membrane and thus allows the introduction of channels or trans-membrane proteins for selective transport.…”
Section: Introductionmentioning
confidence: 99%